Appropriate electrode placement site of electric pulp tester for the premolars: A clinical study - Seema Dinesh Bargale; Shital Kiran Davangere Padmanabh (Wolters Kluwer Medknow Publications, 2015)
Context: Electric pulp testers (EPTs) are widely used as diagnostic aid in dentistry for dental pulp. This delivers enough current to overcome enamel and dentin resistance and to stimulate the myelinated sensory ﬁbers at the junction of pulp and dentin. Such testing requires the electrode to be in contact with the surface of the tooth, with optimal positions identiﬁed for anterior teeth, premolars, and molars. Aims: To determine the best site position of EPT on premolars. The objective of electric pulp testing was to determine the sensibility of each premolar at the lowest sensory response threshold. Settings and Design: Clinical study Materials and Methods: The premolars of 20 patients between 13 and 15 years accompanied with parents, free of restorations, and caries were selected. Five sites on the crown were tested with EPT for minimum of four times. Statistical analysis used: One-way analysis of variance test and the Tukey's honestly significant difference test. Results: The lowest threshold response was noted at the incisal edge of the tooth; the middle third had a higher threshold among all the different placement of electrode. Statistically significant difference was observed for occlusal surface in terms of region of placement of electrode. Conclusions: This experiment found the best electrode site for pulp testing in premolars. The appropriate EPT site was on the occlusal surface of maxillary and mandibular premolars.